Penatalaksanaan Radioterapi pada Kasus Mycosis Fungoides di Rumah Sakit Pusat Kanker Nasional Dharmais: Radiotherapy Management in Mycosis Fungoides Cases at Dharmais National Cancer Center Hospital - Agustria, Rory; Lalu Verry Holistia (MPI Press, 2025)
Introduction: Electron beam radiotherapy is commonly used to treat tumors located near the surface of the body due to its limited tissue penetration. Mycosis fungoides is a type of cutaneous T-cell lymphoma, a rare disease that predominantly affects men over the age of 40. Objectives: To describe the use of electron beam radiotherapy in the treatment of mycosis fungoides at the Radiotherapy Installation of Dharmais Cancer Hospital, Jakarta. Method: This descriptive study was conducted through observations, in-depth interviews, and documentation analysis related to electron beam radiotherapy procedures in a case of mycosis fungoides. Result: Electron beam radiotherapy was administered using a 25 x 25 cm field size. Radiotherapy plays a significant role in treating mycosis fungoides, both in early and advanced stages. Localized and total skin electron therapy can offer effective treatment outcomes. Conclution: Electron beam radiotherapy is an effective modality for treating mycosis fungoides, particularly for lesions located on or near the skin surface, as demonstrated in the case treated at Dharmais Cancer Hospital.